Omotenashi: a relação da hospitalidade com a competitividade dos serviços sob a lente dos stakeholders - YATSU, Liliane Amikura (2017)
The development of this empirical research, of qualitative and quantitative character, began in the observation of the hospitality practiced by the Japanese, the omotenashi. The research question is: How the Japanese style of hospitality influences the competitiveness in services under the lens of stakeholders? Within this context, this research has as main objective to identify the relationship of hospitality based on the omotenashi with the competitiveness of services from the host's point of view, which in this case is the company and as specific objectives the aim is to study the conceptualization of hospitality, understand the omotenashi and verify how the relation between hospitality and omotenashi can bring competitive advantage in the provision of services of a company. Three propositions were created: (P1) The competitiveness of a Japanese organization in Brazil when it adopts omotenashi is perceived by the client. (P2) For the Japanese citizen the omotenashi is not a differential, due it is already part of the culture, therefore, of his daily life. (P3) The Japanese have a different point of view of what is to be hospitable, but they do their best to attend and satisfy the others. The research methodology is an empirical, qualitative and exploratory research, adopting the multiple case study method as proposed by Yin (2005). The collection of evidences was held through bibliographic research, documents and through a survey developed in 2015 by the authors Asli D. A. Tasci and Kelly J. Semrad, of University of Central Florida, which was translated to Japanese and interviews. The proposed research protocol was developed with the characterization method proposed by Bardin (2011), which served as a basis for further content analysis of the content generated by the survey and interviews.